2012
DOI: 10.2459/jcm.0b013e3283569774
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for catheter ablation of atrial tachycardia following atrial fibrillation ablation

Abstract: The increased acquisition speed by AFocusII DL facilitated the reconstruction of the geometric chamber, and the generation of an isochronal activation map reduced processing time and fluoroscopy time per patient, together with the radiation exposure and patient radiation dose. A novel algorithm combining both conventional electrophysiology and a three-dimensional electroanatomic approach for rapid diagnosis, accurate mapping and ablation of iatrogenic atrial tachycardias showed high reproducibility and a satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Faustino et al observed in 40 patients presenting with AT after previous ablation for paroxysmal or persistent AF (using a stepwise approach) that of 75 tachycardias 48 were macroreentries and 27 were focal. 19 Rostock et al investigated 320 patients undergoing ablations for AT (following an ablation for persistent AF using a stepwise approach) and reported that 72% of ATs were reentrant, whereas 28% were classified as focal. 20 Predictors of recurrence were not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faustino et al observed in 40 patients presenting with AT after previous ablation for paroxysmal or persistent AF (using a stepwise approach) that of 75 tachycardias 48 were macroreentries and 27 were focal. 19 Rostock et al investigated 320 patients undergoing ablations for AT (following an ablation for persistent AF using a stepwise approach) and reported that 72% of ATs were reentrant, whereas 28% were classified as focal. 20 Predictors of recurrence were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Faustino et al . observed in 40 patients presenting with AT after previous ablation for paroxysmal or persistent AF (using a stepwise approach) that of 75 tachycardias 48 were macroreentries and 27 were focal . Rostock et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because this was the first study investigating the clinical use of the new MBC, we enrolled only patients with right‐sided ATs to evaluate the safety of using the MBC. Previous studies have reported the utility of multielectrode catheters with NavX for activation mapping of left‐sided AT . In our opinion, rapid mapping with the new MBC might also be useful for understanding AT circuits in the left atrium.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have reported the utility of multielectrode catheters with NavX for activation mapping of left-sided AT. [20][21][22][23] In our opinion, rapid mapping with the new MBC might also be useful for understanding AT circuits in the left atrium.…”
Section: Left Atrial Accessmentioning
confidence: 99%